1990
DOI: 10.1007/bf00230857
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and disynaptic excitatory inputs from the superior colliculus to vertical saccade-related neurons in the cat Forel's field H

Abstract: Excitatory inputs to neurons in the Forel's field H (FFH) related to visually induced vertical saccades from the ipsilateral superior colliculus (SC) were investigated in chronically prepared alert cats. By stimulation of the deep or intermediate layer of the SC, upward augmenting neurons (ANs) and one long-lead downward burst neuron (BN) were found to be activated monosynaptically, while medium-lead BNs were activated disynaptically. The monosynaptically activated neurons were not antidromically activated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 13 publications
2
9
1
Order By: Relevance
“…Reports in which riMLF cells were intracellularly injected with horseradish peroxidase (Moschovakis et al, 1991b) illustrate multipolar cells, some of which appear similar to our type I cells. These burst neurons project to both iC and OC (Moschovakis et al, 1991a), which is consistent with the findings of Nakao et al (1990) that burst neurons project to OC monosynaptically.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Reports in which riMLF cells were intracellularly injected with horseradish peroxidase (Moschovakis et al, 1991b) illustrate multipolar cells, some of which appear similar to our type I cells. These burst neurons project to both iC and OC (Moschovakis et al, 1991a), which is consistent with the findings of Nakao et al (1990) that burst neurons project to OC monosynaptically.…”
Section: Discussionsupporting
confidence: 89%
“…The introduction of new tract-tracing techniques in the past 20 years has revealed that the ND has no direct connection with the oculomotor system (Graybiel and Hartwieg, 1974;Steiger and Buttner-Ennever, 1979). However, another region has been revealed at the rostral end of the MLF, contiguous with the rostral iC (Buttner-Ennever and Buttner, 1978;Graybiel, 1977b), which contains neurons that discharge before and during vertical saccadic eye movements (Buttner et al, 1977;King and Fuchs, 1979;King et al, 1981;Nakao et al, 1990). This region has received different designations (for review, see Buttner-Ennever and Biittner, 19881, but it is most commonly termed the "rostral interstitial nucleus of the MLF" (riMLF).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The ascending projection from tectofugal neurones is interesting also with respect to eye motor control since it has been shown that the target neurones project to the frontal eye field (area 8) and the inferior parietal lobule (area 7; Harting, Huerta, Frankfurter, Strominger & Royce, 1980). Mono-and disynaptic excitatory connections from tectofugal neurones to vertical saccade-related neurones have recently been observed in the fields of Forel (Nakao, Shiraishi, Li & Oikawa, 1990). Furthermore, it has been shown by Isa, litouji, Nakao & Sasaki (1988a) and Isa, litouji & Sasaki (1988b) that excitatory neurones in the fields of Forel project monosynaptically or disynaptically via reticulospinal neurones to dorsal neck motoneurones.…”
Section: Discussionmentioning
confidence: 99%